2015
DOI: 10.5933/jkapd.2015.42.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Treatment Parameters for Photodynamic Antimicrobial Chemotherapy on <italic>Streptococcus mutans</italic> Biofilms

Abstract: The purpose of this study was to evaluate the effects of Photochemotherapy using a combination of erythrosine and standard halogen dental curing lights on the viability of Streptococcus mutans in the biofilm phase. To investigate the optimum treatment parameters, the researchers controlled the concentration of erythrosine, light irradiation time and the treatment time of erythrosine. The higher concentration of erythrosine (0, 10, 20, 40, 80 M) in the presence of light irradiation created greater effects in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In this study, the total irradiation time was set as 15 minutes. The energy of photodynamic therapy with erythrosine, which was most effective with halogen light, was observed to be above 18 J [12,13]. Since the output of the home whitening In our study, aPDT groups showed 95% reduction in planktonic states, whereas in dynamic biofilm state, the reduction rate ranged from 53% to 61%.…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 53%
See 1 more Smart Citation
“…In this study, the total irradiation time was set as 15 minutes. The energy of photodynamic therapy with erythrosine, which was most effective with halogen light, was observed to be above 18 J [12,13]. Since the output of the home whitening In our study, aPDT groups showed 95% reduction in planktonic states, whereas in dynamic biofilm state, the reduction rate ranged from 53% to 61%.…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 53%
“…In this study, erythrosine (Sigma-Aldrich, St. Louis, MO, USA) was chosen as a photosensitizer. The erythrosine concentration was 20 μM/L and it was prepared in phosphate buffered saline (PBS, pH 7.4), sterilized by filtration, covered in an aluminum foil, and stored at -20°C [11][12][13].…”
Section: Photosensitizer and Light Sourcementioning
confidence: 99%
“…Erythrosine is effective in the treatment of intraoral bio-films [12]. PDT using a halogen curing unit and erythrosine for S. mutans biofilms optimized the concentration of erythrosine (> 20 -40 μM) and application time (>2.5 min) for the prevention of dental caries [20].…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…In this study, 18 J/cm 2 of energy was irradiated in all light sources. The optimal dental caries preventive effect in PDT using erythrosine and halogen has been determined to be an irradiation time exceeding 30 s, with an energy output of the halogen of 600 mW/cm 2 [20]. Presently, the result of PDT was the same for the three groups with the same amount of energy was used along with photosensitizer.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation